SOSIALISASI DAN PENDAMPINGAN MASYARAKAT DALAM UPAYA MENINGKATKAN KEPATUHAN DALAM MEMBAYAR IURAN JAMINAN KESEHATAN NASIONAL - Fadila, Rizki; Dewiyani, AAI Citra; Ardhiasti, Anggi (Politeknik Kesehatan Kemenkes malang, 2023)
One of the challenges faced by BPJS Kesehatan in implementing the JKN program is that there are still many JKN participants who are in arrears in paying their monthly JKN contributions. Community service activities aim to increase community compliance in paying National Health Insurance contributions, increase public knowledge about the importance of paying JKN contributions on time, and increase public understanding of the mechanisms and procedures for paying JKN contributions and paying JKN fines. The implementation method is carried out by applying pre-test, socialization, mentoring, question and answer and post-test. The target of the activity is 59 community members who are in arrears in paying JKN contributions in Tumpang District, Malang Regency. Community service activities have a positive impact on the community in Tumpang District, Malang Regency. The implementation of socialization and mentoring activities is able to increase public knowledge about the JKN program and increase public awareness to pay JKN contributions on time.